(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
this article examines important aspects of the concept of telemedicine services and their legal regulation. The relevance of the study of telemedicine services is due to their growing role in the healthcare system, the need to form effective mechanisms for regulating this area, as well as the presence of a number of unresolved legal, organizational and ethical issues related to the provision of medical care remotely. The purpose of this article is a comprehensive analysis of the concept of telemedicine services, their classification and features of legal regulation, as well as identifying the main trends and problems in the development of this area.